Radioactivity and Space Range of Ultra-Low-Activity for in vivo Off-line PET Verification of Proton and Carbon Ion Beam—A Phantom Study - Zhang, Fuquan; Zhang, Junyu; Lu, Yan; Sheng, Yixiangzi; Sun, Yun; Zhang, Jiangang; Cheng, Jingyi; Zhou, Rong (Frontiers in Public Health, 2021)
Purpose: The induced radioactivity triggered by proton and heavy ion beam belongs to the ultra-low-activity (ULA). Therefore, the radioactivity and space range of commercial off-line positron emission tomography (PET) acquisitions based on ULA should be evaluated accurately to guarantee the reliability of clinical verification. The purpose of this study is to quantify the radioactivity and space range of off-line PET acquisition by simulating the ULA triggered by proton and heavy ion beam. Methods: PET equipment validation phantom and low activity 18F-FDG were used to simulate the ULA with radioactivity of 11.1-1480 Bq/mL. The radioactivity of ULA was evaluated according to comparing the radioactivity in the images with the values calculated from the decay function with an error tolerance of 5%; The space range of ULA was evaluated according to comparing the width of the R50 analyzed activity distribution curve with the actual width of the container with an error tolerance of 4mm. Results: When radioactivity of ULA was greater than 148 Bq/mL, the error was less than 5%. When radioactivity of ULA was greater than 30 Bq/mL, the space range error was below 4 mm. Conclusions: Off-line PET can be used to quantify the induced radioactivity of proton and heavy ion beam when the ULA exceeds 148 Bq/mL, both in radioactivity and in space range.